Discriminant analysis of multi sensor data fusion based on percentile forward feature selection - Maz Jamilah, Masnan (2017)
Feature extraction is a widely used approach to extract significant features in multi sensor data fusion. However, feature extraction suffers from some drawbacks. The biggest problem is the failure to identify discriminative features within multi-group data. Thus, this study proposed a new discriminant analysis of multi sensor data fusion using feature selection based on the unbounded and bounded Mahalanobis distance to replace the feature extraction approach in low and intermediate levels data fusion. This study also developed percentile forward feature selection (PFFS) to identify discriminative features feasible for sensor data classification. The proposed discriminant procedure begins by computing the average distance between multi- group using the unbounded and bounded distances. Then, the selection of features started by ranking the fused features in low and intermediate levels based on the computed distances. The feature subsets were selected using the PFFS. The constructed classification rules were measured using classification accuracy measure. The whole investigations were carried out on ten e-nose and e-tongue sensor data. The findings indicated that the bounded Mahalanobis distance is superior in selecting important features with fewer features than the unbounded criterion. Moreover, with the bounded distance approach, the feature selection using the PFFS obtained higher classification accuracy. The overall proposed procedure is found fit to replace the traditional discriminant analysis of multi sensor data fusion due to greater discriminative power and faster convergence rate of higher accuracy. As conclusion, the feature selection can solve the problem of feature extraction. Next, the proposed PFFS has been proved to be effective in selecting subsets of features of higher accuracy with faster computation. The study also specified the advantage of the unbounded and bounded Mahalanobis distance in feature selection of high dimensional data which benefit both engineers and statisticians in sensor technology